Pengaruh Latihan Passing ke Dinding terhadap Kemampuan Passing Atas Bola Voli pada Ekstrakurikuler MTs Negeri 4 Kebumen Tahun Ajaran 2024/2025: Penelitian - Puput Widodo; Arfi Hasan; Arwan Adik Priyanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
MTs Negeri 4 Kebumen, which has an active volleyball extracurricular program, the results of observations show that basic skills such as overhead passing still need to be improved. This study aims to measure the effect of drill passing exercises with wall media on the overhead passing ability of students participating in extracurricular activities. This study uses a